Distribution areas of quarantine plant pest organisms of the fruit fly Bactrocera musae (Diptera: Tephritidae) in South Sulawesi, Indonesia - Junaidi, Junaidi; Gassa, Ahdin; Ramli, Ramli; Patandjengi, Baharuddin (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Bactrocera musae is one of the most damaging fruit fly species affecting tropical fruit crops, particularly bananas. In Indonesia, this species is classified as an A2 Quarantine Plant Pest due to its economic impact and potential to spread into key production and export regions. However, updated information on its spatial distribution in South Sulawesi remains limited. This study aimed to map the occurrence and distribution of B. musae through field surveillance. Fruit fly specimens were collected using traps baited with methyl eugenol and installed across selected survey locations representing fruit-producing areas. Morphological identification was performed using standard taxonomic keys for Bactrocera species. The survey results confirmed that the distribution of B. musae in South Sulawesi is relatively extensive. The pest was detected in Makassar City and the regencies of Gowa, Takalar, Jeneponto, Bulukumba, Bantaeng, Sinjai, and Bone. These areas are characterized by the presence of tropical fruit crops, including banana, mango, guava, and papaya, which may serve as suitable host plants and support population establishment. The confirmed presence of B. musae in multiple regions indicates the need for strengthened surveillance, early detection programs, and quarantine measures. The findings of this research provide important baseline data for future pest risk analysis and policy development, particularly regarding pest status determination and preventive actions in South Sulawesi and other vulnerable regions. Further studies on population ecology, host interactions, and management strategies are recommended to support more effective control efforts.